’Grandfluencers’: How Older Adults Reinvent themselves on TikTok - Arias Montesinos, Sandra; Ramos Soler, Irene; Campillo Alhama, Concepción (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
In a global context where population aging is an increasing reality, social media platforms are emerging as spaces where older adults can engage in the public sphere, taking on roles that challenge ageist stereotypes. This study examines the use of TikTok as a communication channel for older adults with a presence and influence on the social network. The objective is to categorize their messages and understand which types generate the most engagement and among which audiences, linking this visibility to the dismantling of negative stereotypes associated with older adults. To this end, a content analysis was conducted on 11 TikTok profiles of grandfluencers in Spain. The findings were cross-referenced with in-depth interviews with related professionals and the grandfluencers themselves. The phenomenon of grandfluencers is particularly significant as it fosters intergenerational interactions that can break down age-related prejudices. Grandfluencers employ creative strategies, such as humor and storytelling, to emotionally connect with their followers, helping to normalize generational diversity in digital spaces predominantly occupied by younger people. Additionally, this study could have significant implications for the design of inclusive policies and communication strategies that promote intergenerational equity and active aging.